Reduction in Placental Metal and Metalloid in Preeclampsia: A Case–Control Study - Hao, Yanhui; Yu, Wen; Wu, Jiaying; Yue, Yingyu; Wu, Yanting; Huang, Hefeng; Wu, Weibin (Nutrients, 2024)
Preeclampsia is a primary placental disorder, with impaired placental vascularization leading to uteroplacental hypoperfusion. We aimed to investigate differences in metal and metalloid content between the placentas of women with preeclampsia and healthy controls. This was a case–control study in 63 women with preeclampsia and 113 healthy women. Clinical data were obtained from medical records. Inductively coupled plasma mass spectrometry (ICP-MS) was used to measure the placental metals and metalloids content. Compared with healthy control subjects, preeclampsia was associated with a significantly lower concentration of essential elements (magnesium, calcium, iron, copper, zinc, and selenium) in the placental tissue. After multivariable adjustment, an interquartile range (IQR) increase in selenium concentration was associated with a reduced risk of preeclampsia with an OR of 0.50 (95% CI: 0.33–0.77). The joint effects of multiple selected metals and metalloids were associated with a reduced risk of preeclampsia. The lower placental magnesium, chromium, iron, zinc, and selenium concentrations of preeclampsia cases indicate a potential link to its pathogenesis. It also provides an intriguing avenue for future research in revealing the underlying mechanisms and potential intervention strategies for preeclampsia.